Performance assessment of an electricity system and its improvement measures : the case of Java-Bali system, Indonesia - Rasional Sitepu; Heredia , J.B.; Giap, Van Dang; Yu, Cun Yi; Malik, Arif Saeed; Higher Education Development Project (Proyek PS2PT) of Indonesia (Bangkok : Asian Institute of Technology, 1995)
In this study, performance of the electricity system of Java Bali, Indonesia during the period of 1983-1994 is analyzed. The analysis involves technological, financial, economic and social aspects. Indicators that relate to those aspects are selected. Such indicators are selected because they are commonly used internationally in the performance evaluation of electricity system industries. The method used for the analysis of this study is the ratio method, which is also called the engineering method. This method has some advantages i.e., it is simple, easy to understand, can cover whole aspects of performance, data is available whether in time series or in cross sectional form, and can be used quickly. The weakness in the method is that it cannot account for interdependence. In order to make use of this method and indicators, an amount of secondary data had to be gathered from various offices of PT. PLN (Persero), the state enterprises for electricity of Indonesia, and from the ES CAP office in Bangkok. It is found that the performance of the Java Bali electricity system is favorable and comparable for the all aspects analyzed. It is identified also that there are opportunities to improve the efficiency of power plants and operation costs. From the technical point of view, overall the Java Bali system tended to improve especially during the last six to seven years. The financial performance of the utility was relatively good. Finally, economic and social performance has shown improvement. However, there is a drawback of the system as well at the utility level. For example, the limitation of the power supply and the unpredictability of the growth of demand, have made some of the thermal power plants utilized above its nominal rate. Inadequacy of management, particularly in coordination of construction planning has caused a bottle neck between the generation side and demand side. For this some measures are recommended to improve the performance.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1995
Keywords: Electric power systems -- Indonesia